A brief discussion on the secondary prevention of ischemic stroke - Sheng-nian ZHOU; Wei JIANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2015)
DOI: 10.3969/j.issn.1672-6731.2015.03.001